The Role of the National Elections Commission in Ensuring the Rights and Obligations of the Community to Participate in the 2023 Parliamentary Elections in Timor Leste - Adao SOARES; William DJANI; Ajis Salim Adang DJAHA (International Journal of Environmental, Sustainability, and Social Science, 2025)
The National Election Commission or Comissão Nacional da Eleições abbreviated as CNE is an independent institution/body that organizes national elections, meaning that the Comissão Nacional de Eleições (CNE) is one of the central institutions in Timor Leste tasked with supervising, organizing, managing and organizing General Elections as an instrument to realize the sovereignty of the people, form a legitimate government and as a means of articulating the aspirations and interests of the people. The role of the Comissão Nacional de Eleições (CNE) in organizing and supervising, organizing and managing the National Parliamentary Elections has provided guarantees and opportunities for citizens to convey their voices and elect leaders who will represent them in government. In the General Election, eligible citizens have the right to cast their votes for the candidates or political parties of their choice. The election results are then used to determine who will hold political office, either at the local, regional or national levels through the winning party in the election. The purpose of this study is to describe and analyze the role of the Comissão Nacional de Eleições in ensuring the rights and obligations of the community to participate in the General Election, Parliamentary Election in 2023 in Timor-Leste. The method used to examine the research problem is a qualitative descriptive approach. While data collection techniques include observation, document studies, and interviews, while data analysis techniques include the stages of data collection, data reduction, data presentation, and drawing conclusions.